Circular Economy Business Models in the Micro, Small, and Medium Enterprises: A Review - Astadi Pangarso; Kristina Sisilia; Yahya Peranginangin (ETIKONOMI, 2022)
MSME business should be built based on circular economy (CE)-based business models. The purpose of this article is to presenta review of several articles that have been published in Scopusdiscussing the CE-based business model and MSMEs to findresearch gaps and future research agendas. It used some tools of thetheoretical assay, such as bibliometric analysis, systematic literaturereview, theory, context, and characteristic methodology (TCCM).The paper outlines all findings of analyzed literature about CE’sbusiness model applied by MSME in the Scopus document untilJune 2021. The findings of this study provided more high-qualityevidence about research and practical gaps regarding the CE-basedbusiness model and MSME, which needs more research focuseson market desirability in the future and more understanding ofinternal processes in MSME’s case studies. The implication of thisarticle is to provide a future research agenda based on a collectionof research gaps as a basis for empirical research.JEL Classification: L26, M10, Q56